2015
DOI: 10.1152/ajpheart.00546.2015
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic pulmonary exposure and systemic cardiovascular response via neurological links

Abstract: The cardiovascular response to xenobiotic particle exposure has been increasingly studied over the last two decades, producing an extraordinary scope and depth of research findings. With the flourishing of nanotechnology, the term "xenobiotic particles" has expanded to encompass not only air pollution particulate matter (PM) but also anthropogenic particles, such as engineered nanomaterials (ENMs). Historically, the majority of research in these fields has focused on pulmonary exposure and the adverse physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 130 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Adverse health effects include eye and throat irritation, inflammation, pulmonary disease, and reduced or impaired cognitive function. Multiple organs and systems are known to be targeted by toxic airborne exposures, including blood, lungs, cardiovascular, and central nervous systems [34][35][36][37]. One of the most intensely tested concepts concerning health effects of exposure to airborne toxins is that the onset of inflammatory responses mediates the causal path from pulmonary exposure to development of pulmonary, cardiovascular, metabolic, malignant, and neurodegenerative diseases [29,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse health effects include eye and throat irritation, inflammation, pulmonary disease, and reduced or impaired cognitive function. Multiple organs and systems are known to be targeted by toxic airborne exposures, including blood, lungs, cardiovascular, and central nervous systems [34][35][36][37]. One of the most intensely tested concepts concerning health effects of exposure to airborne toxins is that the onset of inflammatory responses mediates the causal path from pulmonary exposure to development of pulmonary, cardiovascular, metabolic, malignant, and neurodegenerative diseases [29,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is little consensus regarding the safety of engineered nanomaterials, the mechanisms by which they may induce a toxic response, or how these mechanisms may be influenced by particle size or modifications such as addition of capping agents. There is current literature evidence that pulmonary exposure to PM and ENMs can alter to progression of or to cardiovascular disease (CVD) and dysfunction through multiple pathways, including inflammation [ 15 , 33 , 36 ], autonomic dysfunction [ 25 , 37 , 38 ], oxidative stress [ 39 41 ] or mitochondrial dysfunction [ 42 , 43 ]. We evaluated the impact of a pulmonary exposure to 2 different sized silver nanoparticles (AgNP) with different capping agents on pulmonary BAL cells and protein, serum cytokine (as a surrogate for systemic inflammation), protein oxidation in lung and heart, vascular function, and myocardial ischemia reperfusion (I/R) injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of evidence about the toxic effects and mechanisms induced by AgNPs on heart is limited, there are much fewer investigations on the impeding effects of these nanoparticles on populations with cardiovascular pathologies such as hypertension. In this regard, previous studies have demonstrated that pulmonary exposure to engineered nanomaterials is capable of aggravating cardiovascular dysfunction via mechanisms including systemic inflammation, coronary artery dysfunction, metabolic derangement, autonomic dysregulation, and oxidative stress [15][16][17][18]. Oxidative stress contributed by increased reactive oxygen species level generates an imbalance between reactive oxygen species generation and antioxidant defence mechanism such as catalase and superoxide dismutase [19].…”
Section: Introductionmentioning
confidence: 99%